Influência dos coquetéis enzimáticos produzidos por Trichoderma reesei e Aspergillus niger pelo processo de fermentação sequencial na hidrólise do bagaço de cana-de-açúcar - Florencio, Camila (2016)
Currently, one of the major challenges for second generation ethanol is to reduce the cost of cellulolytic enzymes. Thus, the development of bioprocesses for the enzyme production on-site and strategies to increase the final yield of the enzymatic hydrolysis are required to ensure that biomass conversion to be economically feasible. Therefore, the objective of this work was to study the production and characterization of enzyme cocktails involved in the degradation of plant biomass by filamentous fungi Trichoderma reesei and Aspergillus niger grown in sequential fermentation and evaluate the application of these cocktails in the saccharification process of sugarcane bagasse. Firstly, evaluation and validation of sequential fermentation cultivation methodology to different strains of Trichoderma. Cultivation were made using sugarcane bagasse "in natura" and pretreated by steam explosion, as a carbon source. The result more significantly was observed for T. reesei Rut C30, the endoglucanase production was 4.2-fold higher than the values obtained in conventional submerged fermentation. The enzyme extracts were characterized in terms of optimum pH and temperature and endoglucanase profile. The thermostability was directly influenced by the type of carbon source and type of cultivation method. Subsequently, the proteomic analysis were performed of enzyme cocktails from T. reesei Rut C30 and A. niger A12 produced by submerged and sequential fermentation in the presence of pretreated bagasse. The performance of the enzyme cocktail in saccharification of pretreated bagasse showed that the combination of enzyme cocktails from T. reesei and A. niger produced by sequential fermentation had a yield than 3-fold higher than the enzyme cocktails of submerged fermentation. In order to evaluate the action of the enzyme cocktails produced by T. reesei and A. niger in sugarcane bagasse saccharification, the last step of the work was to study the additives effects during the sugarcane bagasse hydrolysis aiming at reducing non-productive adsorption of enzymes into lignin. The saccharification results in the presence of soybean protein were 2-fold higher than the controls (no additive) to the enzyme cocktails of two fungi studied produced by solid state fermentation, indicating the potential use of soybean protein as an additive to minimize non-productive adsorption of the enzyme into lignin. Overall, this study presents an interesting final contribution in the cellulase production process and the application of the enzyme cocktail in the hydrolysis of sugarcane bagasse.